2020
DOI: 10.1021/acs.chemmater.0c03126
|View full text |Cite
|
Sign up to set email alerts
|

Improved Eco-Friendly Photovoltaics Based on Stabilized AgBiS2 Nanocrystal Inks

Abstract: AgBiS2 nanocrystals (NCs) have emerged as attractive absorbers in eco-friendly photovoltaics because of their nontoxic components and high absorption coefficient. Native long-chain ligands of AgBiS2 NCs should be replaced with short-chain ligands for their photovoltaics; however, conventional approaches have been performed using solid-state ligand exchange (SSLE), resulting in inhomogeneous NC aggregation, broad bandtail, large trap density, and resultantly low open-circuit voltage (V OC) in devices. Herein, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 54 publications
2
45
0
Order By: Relevance
“…The performance reported here is significantly higher than previously reported ink based devices, indicating the superiority of our MPA based solution-phase ligand-exchange method. [7] The J sc value was also estimated from external quantum efficiency (EQE) spectra (Figure 3e), which showed an integrated current density of 24.7 mA cm −1 , [2] in good agreement with the J sc from J-V curve measurements. After storage in ambient air under an average humidity of 30% for one month without encapsulation, the high performance device retained more than 95% of the original efficiency, which confirms the robustness of our nanocrystal inks.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…The performance reported here is significantly higher than previously reported ink based devices, indicating the superiority of our MPA based solution-phase ligand-exchange method. [7] The J sc value was also estimated from external quantum efficiency (EQE) spectra (Figure 3e), which showed an integrated current density of 24.7 mA cm −1 , [2] in good agreement with the J sc from J-V curve measurements. After storage in ambient air under an average humidity of 30% for one month without encapsulation, the high performance device retained more than 95% of the original efficiency, which confirms the robustness of our nanocrystal inks.…”
Section: Introductionsupporting
confidence: 65%
“…[6] Currently, the most widely used solvents in solution-phase ligand-exchange procedures are formamide (FA), N,N-dimethyl formamide (DMF) and dimethyl sulfoxide (DMSO). [3,[7][8][9] However, these polar solvents are highly toxic, raising major concerns on overall environmental impact. [10] Moreover, occupational safety must be taken into account for operators in manufacturing or scientists in the lab, who may come into direct contact with the ink or inhale solvent fumes during fabrication.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Similarly, attention has been devoted to optimising the ligand exchange procedure, which can be performed either in a layer-by-layer fashion 12,14 or via a liquid phase exchange. 15,16 Alternatively, it has been shown that the ligand exchange step can be omitted by directly synthesising the nanocrystals with the final ligands. 17 While these efforts are very important for further improving the performance of AgBiS 2 PVs, very little is known about the stability of these devices.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years there has been a remarkable progress in the synthesis and application of colloidal AgBiS 2 nanocrystals as the photoactive material in solar cell devices. 7,11,12,[17][18][19][20][21][22][23]24 The low carrier diffusion length and the non-negligible recombination pathways have been identified as the main limiting factors for photocurrent generation, especially when using thick active layers. 7,12 Therefore, the record solar cell efficiencies reported so far typically limit the optimal AgBiS 2 layer thickness at around 35 nm.…”
Section: Enhanced Solar Cell Performancementioning
confidence: 99%